Multi-year training of young athlete as potential modifyer of growth and development (Analysis of some biological concepts) - Vorontsov, A. R. (coachesinfo.com)
Actual physical, technical and psychological potential of the athletes is formed from inborn abilities in the process of multi-year training (MYT). It is commonly presumed, that being properly organised and conducted MYT may be used as a powerful and purposeful modifier of natural growth and development.